Respuesta :
product of complex numbers (-3i +4) and (3i +4)
(x - y)(x + y) = x² - y²
(-3i +4)(3i +4) = (4 -3i )(4 + 3i) = 4² - (3i)² = 16 - 9*(-1)=16 + 9 = 25
(x - y)(x + y) = x² - y²
(-3i +4)(3i +4) = (4 -3i )(4 + 3i) = 4² - (3i)² = 16 - 9*(-1)=16 + 9 = 25
Answer:
[tex](-3i+4)*(3i+4)=25[/tex]
Step-by-step explanation:
1. First writhe the complex numbers to multiply:
[tex](-3i+4)*(3i+4)[/tex]
2. Multiply the first term of the first parentheses by the first term of the second parentheses:
[tex]-3i*3i=-9i^{2}[/tex]
3. Multiply the first term of the first parentheses by the second term of the second parentheses:
[tex]-3i*4=-12i[/tex]
4. Multiply the second term of the first parentheses by the first term of the second parentheses:
[tex]4*3i=12i[/tex]
5. Multiply the second term of the first parentheses by the second term of the second parentheses:
4*4=16
6. Write all the terms:
[tex](-3i+4)*(3i+4)=-9i^{2}-12i+12i+16[/tex]
7. Add up the terms:
[tex](-3i+4)*(3i+4)=-9i^{2}+16[/tex]
8. As [tex]i^{2}=-1[/tex]:
[tex](-3i+4)*(3i+4)=-9(-1)+16\\(-3i+4)*(3i+4)=9+16\\(-3i+4)*(3i+4)=25[/tex]